Internalizing Islamic Values in Students: The Role of Character Education in Building Morals and Ethics - Mahfud, Moh.; Sofiatus Zahriyah (MA'ALIM: Jurnal Pendidikan Islam, 2025)
This article discusses the importance of character education in Islamic education to strengthen students' morals and ethics. In Islamic education, character education aims not only to transfer religious knowledge to students but also to prepare them to be virtuous individuals, possessing high morality, and practicing ethics in daily life. However, there are challenges in strengthening students' morals and ethics through character education, such as the negative influence of the surrounding environment, social media, and rapid social changes. This research uses a literature review method to support the understanding of character education in Islamic education. This article is expected to contribute to the understanding and development of character education in Islamic education. This article highlights the importance of character education in Islamic education and several factors that influence it, such as the role of teachers, teaching methods, the role of family and community, assessment and evaluation, contextual character education programs, as well as policies and guidelines that support the implementation of character education.